Stop TB a comparative analysis of Tuberculosis communication campaigns of World Vision, Reachout Foundation, and Department of Health - Martinez, Elaine (2006)
This research focused on the Tuberculosis communication campaigns launched from 2001 to 2005. There were four institutions that were studied. ReachOut Foundation International, the Department of Health and World Vision Development Foundation's Kusog Baga Project and Social Mobilization for TB Project. Qualitative and quantitative methods of research were used for the study. Interviews among key informants from respective organizations and projects were done to find out the different processes involved in the conceptualization, production and implementation of the communication campaigns while content analysis was used to evaluate all the IEC materials that were produced as part of the communication campaign. The results of the study revealed several similarities in the campaigns launched by the ReachOut Foundation, DoH and World Vision. Among these are the series of analyses and strategic planning in the development of the communication campaigns; communication objectives; target audience; stakeholders and different channels used in IEC materials. The results also showed that majority of the materials produced were print materials such as posters, billboards, comics , stickers and flipcharts. Video materials such as television public service announcements and video orientation materials come next as the most common form of IEC materials that were produced. Institutions studied demonstrated several strengths on how they implemented their communication campaigns. The strengths identified are: networking and building partnerships for resource mobilization; mobilizing, communities for localized communication efforts and follow-up support of campaigns; consulting TB experts for technical accuracy of IEC materials; strengthening of community based media efforts for wider coverage of communication efforts. Some of the recommendations of the study are for various projects and TB stakeholders to come up with an integrated communication strategy to guide them in coming up with standardized communication messages of themes and to fully utilize radio and television channels for communication efforts.